2018
DOI: 10.1177/2374373518793143
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience in Primary Care: A Systematic Review of CG-CAHPS Surveys

Abstract: The National Academy of Medicine’s (NAM) vision for 21st-century health care underscored the need for increased patient engagement and charged health-care researchers to develop tools to evaluate patient experience. The most widely studied patient experience tools are the Consumer Assessments of Healthcare Providers and Systems (CAHPS) surveys. The Clinician and Group (CG)-CAHPS survey is the preferred patient experience survey for primary care, and thus a systematic review of patient reports from the CG-CAHPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…It is also of interest that no differences were observed between male or female patients for this area, contrary to another study showing female patients VA providing lower ratings on communication, trust, and care quality (18). Increasing age had a strong effect on higher ratings of access, a finding noted in many studies of patient experience, including primary care (19)(20)(21). Some research has shown that patient expectations and preference change with age.…”
Section: Discussionmentioning
confidence: 86%
“…It is also of interest that no differences were observed between male or female patients for this area, contrary to another study showing female patients VA providing lower ratings on communication, trust, and care quality (18). Increasing age had a strong effect on higher ratings of access, a finding noted in many studies of patient experience, including primary care (19)(20)(21). Some research has shown that patient expectations and preference change with age.…”
Section: Discussionmentioning
confidence: 86%
“…The questions regarding communication effectiveness in the Clinician & Group Consumer Assessment of Healthcare Providers and Systems questionnaire and other questionnaires addressing communication effectiveness are subject to strong ceiling effects (7,8). And they are in some ways too general to lead to direct coaching and training of specific tactics (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this need, CG-CAHPS released a qualitative Patient Elicitation Protocol for the purpose of gathering narrative descriptions from patients about their health care ( 17 ). Thus, while patients’ perspectives on primary care have begun to be explored ( 18 ), the authors could find no published reviews of interprofessional collaboration in primary care (IPC-pc) involving patients’ experiences. The risks, benefits, and outcomes of IPC-pc remain relatively unexplored, from the perspective of patients utilizing this model of care, who are arguably its greatest stakeholders.…”
Section: Introductionmentioning
confidence: 99%